2020
DOI: 10.3390/pathogens10010008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation, Course, and Risk Factors Associated with Mortality in a Severe Outbreak of COVID-19 in Rhode Island, USA, April–June 2020

Abstract: Long-term care facilities (LTCFs) have had a disproportionally high mortality rate due to COVID-19. We describe a rapidly escalating COVID-19 outbreak among 116 LTCF residents in Rhode Island, USA. Overall, 111 (95.6%) residents tested positive and, of these, 48 (43.2%) died. The most common comorbidities were hypertension (84.7%) and cardiovascular disease (84.7%). A small percentage (9%) of residents were asymptomatic, while 33.3% of residents were pre-symptomatic, with progression to symptoms within a media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 39 publications
3
28
1
1
Order By: Relevance
“…In the reported cohort, short-term hospital outcomes of hospital mortality, hospital LOS, and hospital readmission were similar between OAs presenting typically versus atypically. This adds another piece of evidence to the literature, which currently presents an inconsistent picture where most ( 6 , 12 ), but not all ( 13 ), studies show that atypical presentation is related to hospital mortality. On the other hand, patients with typical presentation were more likely than patients with atypical presentation to receive ICU-level care, probably because of the respiratory concerns associated with typical presentations.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the reported cohort, short-term hospital outcomes of hospital mortality, hospital LOS, and hospital readmission were similar between OAs presenting typically versus atypically. This adds another piece of evidence to the literature, which currently presents an inconsistent picture where most ( 6 , 12 ), but not all ( 13 ), studies show that atypical presentation is related to hospital mortality. On the other hand, patients with typical presentation were more likely than patients with atypical presentation to receive ICU-level care, probably because of the respiratory concerns associated with typical presentations.…”
Section: Discussionmentioning
confidence: 85%
“…In a smaller and older sample (73 hospitalized OAs, aged 80 and older) in New York State ( 8 ), atypical presentations included altered mental status (36%), generalized weakness (38%), and falls (14%). One hundred and eleven residents of long-term care facilities in the United States presented most commonly with loss of appetite (61.3%), lethargy (42.3%), and increased agitation (38.7%) ( 6 ). In a study ( 7 ) of 817 OA patients presenting to the emergency department in the United States with COVID-19, delirium was the sixth most common of all presenting symptoms (28% of the sample), and 16% had delirium as their primary symptom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…Smaller studies, conducted in age groups similar to ours, showed more comparable mortality rates. 15,28,29 A limitation of all these studies is that they lacked a control group, impeding assessment of excess mortality. In this sense, our results add important evidence regarding the profound dangers of COVID-19 in LTCFs, as illustrated by the 7-fold higher mortality.…”
Section: Discussionmentioning
confidence: 99%